Psychological interventions for people with Parkinson's disease in the early 2020s: Where do we stand?. (11th November 2020) - Zarotti, Nicolò; Eccles, Fiona J. R.; Foley, Jennifer A.; Paget, Andrew; Gunn, Sarah; Leroi, Iracema; Simpson, Jane
Abstract : Purpose: To explore the heterogeneity of the literature on psychological interventions for psychological difficulties in people with Parkinson's disease (PD). Methods: A scoping review was performed across five major databases (MEDLINE Complete, PsycINFO, CINAHL, Academic Search Ultimate, and Cochrane Library) up to June 2020. Results: From an initial return of 4911 citations, 56 studies were included, of which 21 were RCTs. A relatively wide range of therapeutic models have been adopted with people with PD, from common therapies such as cognitive behavioural therapy (CBT) and mindfulness, to less frequent approaches, for example, acceptance and commitment therapy (ACT) and psychodrama. The clinical implications of the findings are discussed, and suggestions are provided for future research on intervention studies and key psychological outcomes. Conclusions: CBT appears to be effective in treating depression and sleep disorders in people with PD, while psychoeducation programmes alone should be avoided. The use of CBT to improve anxiety, quality of life, and impulse control, as well mindfulness‐based interventions, should be undertaken with some caution because of insufficient research and inconsistent results. As we enter the new decade, more high‐quality evidence is required for psychological interventions in people with PD in general and to corroborate preliminary positive findings on the adoption of less frequent approaches such as ACT. Practitioner points: Parkinson's disease is a progressive neurodegenerative condition associated with several psychological difficulties which be targeted by psychological interventions. Currently, cognitive behavioural therapy (CBT) can be recommended to treat depression and sleep disorders in people with Parkinson's, while psychoeducation alone should be avoided. Caution is advised regarding the use of CBT and mindfulness‐based interventions to improve anxiety, quality of life, and impulse control. Further evidence is required for less common approaches, such as acceptance and commitment therapy, psychodrama, and EMDR.